Effect of Academic Achievement, Work Experience and Age on Placement of Subordinates - Aprizal Wahyudi Diprata; Kasyful Anwar (Dinasti International Journal of Management Science, 2023)
This article analyzes the influence of academic achievement, work experience, age on the placement of subordinates, so that management in an institution or company is able to place a work position and position according to their functions and expertise. The method of writing this Literature Review article is the library research method, which originates from from online media such as Google Scholar, Mendeley and/or other academic online media. The results of this article are that: 1) Academic achievement influences the placement of subordinates; 2) Work experience influences the placement of subordinates; and 3) Age has an effect on the placement of subordinates. Apart from these 3 exogenous variables that affect the endogenous variables of placement of subordinates there are many other factors including marital status, physical and mental health.